Dynamic characteristics of piezoelectric jetting dispenser with a double spring recovery system. Issue 4 (March 2021) - Deng, Junjun
Abstract: Piezoelectric jetting dispenser is widely used in microelectronic packaging field. The amplification mechanism with flexible hinge is often used in the piezoelectric jetting dispenser. Because the dynamic performance of the dispenser is affected by the deformation of flexure hinge, a model using rigid body amplification mechanism and double spring recovery is proposed in this paper. The mathematical model of the recovery system is established and the dynamic analysis is carried out. The working characteristics of piezoelectric ceramics are analyzed. With the increase of load stiffness, the maximum output force increases and the maximum output displacement decreases. With the decrease of needle stroke, the pressing force between the needle and the nozzle increases. Based on the double spring recovery system, the ADAMS simulation model is established, and the influence of the pre-compression of the double springs on the pressing force between the needle and the nozzle is studied.